Risk of Tuberculosis Reactivation in Patients with Rheumatoid Arthritis, Ankylosing Spondylitis, and Psoriatic Arthritis Receiving Non-Anti-TNF-Targeted Biologics - Ippolito, Giuseppe; Petrone, Linda; Niccoli, Laura; Nannini, Carlotta; Cantini, Fabrizio; Goletti, Delia (Mediators of inflammation, 2017)
Tuberculosis (TB) still represents an important issue for public health in underdeveloped countries, but the use of antitumor necrosis factor agents (anti-TNF) for the treatment of inflammatory rheumatic disorders has reopened the problem also in countries with low TB incidence, due to the increased risk of TB reactivation in subjects with latent tuberculosis infection (LTBI). Over the last 5 years, several non-anti-TNF-targeted biologics have been licensed for the treatment of rheumatoid arthritis, ankylosing spondylitis, and psoriatic arthritis. We reviewed the epidemiology of TB, the role of different cytokines and of the immune system cells involved in the immune response against TB infection, the methods to detect LTBI, and the risk of TB reactivation in patients exposed to non-anti-TNF-targeted biologics. Given the limited role exerted by the cytokines different from TNF, as expected, data from controlled trials, national registries of biologics, and postmarketing surveillance show that the risk of TB reactivation in patients receiving non-anti-TNF-targeted biologics is negligible, hence raising the question whether the screening procedures for LTBI would be necessary.